‘Lotus and the Dagger’: A Reading of Vedantic Nationalism of Sri Aurobindo - Chakraborty, Nilanjan (SARE: Southeast Asian Review of English, 2023)
Sri Aurobindo’s ideas of nationalism are eclectic, deriving their tradition from Hindu spiritualism, the vision of perfection in man as an entity, and intense esoteric realisation in the mystical philosophy of supramental consciousness of the being, as expounded in the Vedas and the Upanishads. Sri Aurobindo’s writings on political philosophy are a continuum, ranging from the utopian socialist ideas in Bande Mataram, a newspaper he edited to present the ideas of social, political, and judicial boycott to counter the British, to the writings of post-1910, when his life took a spiritual turn after years of spiritual realisations and yogic sadhana, where he mixes the power of the proletariat with the power of Vedantic mysticism. Sri Aurobindo’s ‘political vedantism’ is an attempt to restructure the political and social life of a colonised nation so that an indigenous idea of a nation can be constructed in concurrence with the Vedantic concept of society as a manifestation of a collective supremacy in man. Sri Aurobindo accepts spiritual determinism as the central principle of a nation, but at the same time, it is not a static concept to him but a constant movement of progressive self-evolution towards a perfection of the collective consciousness, manifested through the entity called the ‘nation’. This paper proposes to look at the ideas of spiritual nationalism of Sri Aurobindo and establish a dialogue with a nationalism that is neither socialist nor rightist. Keywords: Internationalism, Postnationalism, Supramental consciousness, Eclectic nationalism, Humanism